Long‐term cultivation of Miscanthus and switchgrass accelerates soil organic carbon accumulation by decreasing carbon mineralization in infertile red soil. Issue 9 (27th July 2022) - Fu, Tongcheng; Xu, Yi; Hou, Wei; Yi, Zili; Xue, Shuai
Abstract: Perennial energy crops (PECs) such as Miscanthus spp. and switchgrass ( Panicum virgatum L.) may have particular influence on microbial communities and their functions in soil organic carbon (C) utilization and mineralization (Cm ). In this study, long‐term effects of PECs on Cm and soil hydrolase activities were examined in bulk and rhizosphere soils of Miscanthus and switchgrass grown on a red soil in South China. Long‐term cultivation (10 years) of PECs led to increases in soil organic C (SOC) and the absolute Cm of bulk and rhizosphere soils. Total Cm was correlated with dissolved organic C and dissolved organic nitrogen (N) in red soils. The specific Cm in bulk soils of switchgrass and Miscanthus were decreased by 11.73% and 20.67% comparing with the control group, respectively. Cultivation of PECs led to a relatively high C/N ratio. There was a difference in priming effect on activities of β‐glucosidase (BG), leucine amin peptidase, N‐acetyl‐β‐glucosaminidase (NAG), and phosphatase between rhizosphere and bulk soils. Compared with the control without PECs, BG activity did not change significantly in bulk soils of PECs, whereas NAG activity decreased significantly. Soil microorganisms were generally limited by soil C and phosphorus (P) in the red soil. The C and P limitations were significantly linearly related with relative Cm ( p < 0.05). Phosphorus limitations in microbial communities were lower with PECs than in the control, indicating that cultivation of PECs could provide an optimal nutrient environment for both plants and microorganisms. Thus, long‐term cultivation of PECs increased SOC content but decreased specific Cm rates. However, because C and P limitations remain for plants and soil microbial communities, optimum fertilization is also necessary for sustainable growth of PECs on red soils. Abstract : Long‐term cultivation of Miscanthus and switchgrass leads to a significant increase in soil organic carbon and absolute soil carbon mineralization rate. Enzyme stoichiometric showed there existed carbon and phosphate limitation in infertile red soils for the two crops.